Isolation and characterization of a dual function protein from Allium sativum bulbs which exhibits proteolytic and hemagglutinating activities - Parisi, Monica Graciela (2008)
A dual function protein was isolated from Allium sativum bulbs and was characterized. The protein had a molecular mass of 25-26 kDa under non-reducing conditions, whereas two polypeptide chains of 12.5 ± 0.5 kDa were observed under reducing conditions. E-64 and leupeptin inhibited the proteolytic activity of the protein, which exhibited characteristics similar to cysteine peptidase. The enzyme exhibited substrate specificity and hydrolyzed natural substrates such as α-casein (Km: 23.0 μM), azocasein, haemoglobin and gelatin. It also showed a high affinity for synthetic peptides such as Cbz-Ala-Arg-Arg-OMe-β-Nam (Km: 55.24 μM, kcat: 0.92 s-1). The cysteine peptidase activity showed a remarkable stability after incubation at moderate temperatures (40-50 °C) over a pH range of 5.5-6.5. The N-terminus of the protein displayed a 100% sequence similarity to the sequences of a mannose-binding lectin isolated from garlic bulbs. Moreover, the purified protein was retained in the chromatographic column when Con-A Sepharose affinity chromatography was performed and the protein was able to agglutinate trypsin-treated rabbit red cells. Therefore, our results indicate the presence of an additional cysteine peptidase activity on a lectin previously described.